Synthesis of PAF, an Antifungal Protein from P. chrysogenum, by Native Chemical Ligation: Native Disulfide Pattern and Fold Obtained upon Oxidative Refolding. Issue 38 (23rd August 2013) - Váradi, Györgyi; Tóth, Gábor K.; Kele, Zoltán; Galgóczy, László; Fizil, Ádám; Batta, Gyula
Abstract The folding of disulfide proteins is of considerable interest because knowledge of this may influence our present understanding of protein folding. However, sometimes even the disulfide pattern cannot be unequivocally determined by the available experimental techniques. For example, the structures of a few small antifungal proteins (PAF, AFP) have been disclosed recently using NMR spectroscopy but with some ambiguity in the actual disulfide pattern. For this reason, we carried out the chemical synthesis of PAF. Probing different approaches, the oxidative folding of the synthetic linear PAF yielded a folded protein that has identical structure and antifungal activity as the native PAF. In contrast, unfolded linear PAF was inactive, a result that may have implications concerning its redox state in the mode of action.